Measuring exercise adherence in patients with low back pain: development, validity, and reliability of the EXercise Adherence Scale (EXAS). (3rd July 2022) - Arensman, Remco M.; Geelen, Rianne H.; Koppenaal, Tjarco; Veenhof, Cindy; Pisters, Martijn F.
ABSTRACT: Objectives: To develop an instrument to measure adherence to frequency, intensity, and quality of performance of home-based exercise (HBE) programs recommended by a physical therapist and to evaluate its construct validity and reliability in patients with low back pain. Methods: The Exercise Adherence Scale (EXAS) was developed following a literature search, an expert panel review, and a pilot test. The construct validity of the EXAS was determined based on data from 27 participants through an investigation of the convergent validity between adherence, lack of time to exercise, and lack of motivation to exercise. Associations between adherence, pain, and disability were determined to test divergent validity. The reliability of the EXAS quality of performance score was assessed using video recordings from 50 participants performing four exercises. Results: Correlations between the EXAS and lack of time to exercise, lack of motivation to exercise, pain, and disability were rho = 0.47, rho = 0.48, rho = 0.005, and rho = 0.24, respectively. The intrarater reliability of the quality of performance score was Kappa quadratic weights (Kqw ) = 0.87 (95%-CI 0.83–0.92). The interrater reliability was Kqw  = 0.36 (95%-CI 0.27–0.45). Conclusions: The EXAS demonstrates acceptable construct validity for the measurement of adherence to HBE programs. Additionally, the EXAS shows excellent intrarater reliability and poor interrater reliability for the quality of performance score and is the first instrument to measure adherence to frequency, intensity, and quality of performance of HBE programs. The EXAS allows researchers and clinicians to better investigate the effects of adherence to HBE programs on the outcomes of interventions and treatments.